Influence of COVID-19 Lockdown on Self-Efficacy in Endodontics among Dental Students - Jelena Vidas Hrstić; Ema Paljević; Ivana Brekalo Pršo; Ivana Vidović Zdrilić; Luka Šimunović; Elvis Božac; Romana Peršić Bukmir (Acta Stomatologica Croatica)
Objectives: The aim of this study was to evaluate the change in self-efficacy in endodontics among dental students during their studies and to make a comparison between the generations affected and not affected by the COVID-19 lockdown. Materials and Methods: The Endodontic General Self-Efficacy Scale was used. Data for this longitudinal study were obtained from two generations of students who have completed the same three self-efficacy questionnaires at the end of each academic year over a three-year period. Results: Repeated measurements of each participant revealed a statistically significant difference in self-efficacy level among the three repeated measures over a three-year period (F(1, 580) = 80.226; p < 0.05). The effect size between groups showed a statistically significant difference in self-efficacy in performing endodontic treatments across all three repeated measures (F(1) = 13.958 p < 0.05). The post hoc analysis confirmed the between-group difference (2.838; p < 0.05) in the arithmetic mean between the lockdown-affected and non-lockdown-affected groups. Active participation and length of time in a dental office (between several days and one year of experience) were associated with an increase in self-efficacy. Conclusions: Self-efficacy increased as students progressed in their studies. The self-efficacy of students who were not affected by the lockdown tended to increase; however, in the final year of study, the level of self-efficacy was similar for students affected and not affected by the lockdown. The social persuasion component could explain the alignment in self-efficacy levels. It means that individuals who receive verbal encouragement affirming their abilities to succeed in specific tasks are more likely to exert increased efforts and maintain persistence.